The Price of Virtual Utopia: Ready Player One as American Dream and Dystopian Nightmare - Steiner, Philip (AmLit)
Ernest Cline’s novel Ready Player One (2011) is among the most popular science fiction texts of the twenty-first century. Renowned filmmaker Steven Spielberg directed its movie adaptation in 2018 and following the success of the book and film, Cline published the sequel Ready Player Two in 2020. What renders the novel a prime example of contemporary science fiction is its detailed portrayal of an advanced virtual reality and its possible societal implications. Another key aspect is its bipolar structure, consisting of a dystopian reality defined by ecological and social crisis and the virtual utopia OASIS. This paper will demonstrate that Ready Player One represents virtual reality in a highly intermedial manner via the thematization and transposition of video games, music, and films. As I will showcase, this portrayal of VR is essential regarding the novel’s world-building, its narrative structure, and the depiction of its characters. Furthermore, looking at the implied worldview of the novel, I would argue that the OASIS is shown to be a virtual realization of the American dream, a world in which social outcasts and discriminated minorities find a chance to embrace who they are, make friends, find love, and rise from rags to riches. I will consequently show that the novel’s juxtaposition of utopia and dystopia is specifically tied to its treatment of its themes of identity, friendship, and love, and that it utilizes these focus points to show the possibilities that VR might offer in the future, whilst also underlining the risks it harbors.